Emergence of Hyper-Resistant Escherichia coli MG1655 Derivative Strains after Applying Sub-Inhibitory Doses of Individual Constituents of Essential Oils - Chueca, Beatriz; Berdejo, Daniel; Gomes-Neto, Nelson J.; Pagán, Rafael; García-Gonzalo, Diego (Frontiers in Microbiology, 2016)
The improvement of food preservation by using essential oils (EOs) and their individual constituents (ICs) is attracting enormous interest worldwide. Until now, researchers considered that treatments with such antimicrobial compounds did not induce bacterial resistance via a phenotypic (i.e. transient) response. Nevertheless, the emergence of genotypic (i.e. stable) resistance after treatment with these compounds had not been previously tested. Our results confirm that growth of Escherichia coli MG1655 in presence of sub-inhibitory concentrations of the ICs carvacrol, citral, and (+)-limonene oxide do not increase resistance to further treatments with either the same IC (direct resistance) or with other preservation treatments (cross-resistance) such as heat or pulsed electric fields (PEF). Bacterial mutation frequency was likewise lower when those IC’s were applied; however, after 10 days of re-culturing cells in presence of sub-inhibitory concentrations of the ICs, we were able to isolate several derivative strains (i.e. mutants) displaying an increased minimum inhibitory concentration to those ICs. Furthermore, when compared to the wild type (WT) strain, they also displayed direct resistance and cross-resistance. Derivative strains selected with carvacrol and citral also displayed morphological changes involving filamentation along with cell counts at late-stationary growth phase that were lower than the WT strain. In addition, co-cultures of each derivative strain with the WT strain resulted in a predominance of the original strain in absence of ICs, indicating that mutants would not out-compete WT cells under optimal growth conditions. Nevertheless, growth in the presence of ICs facilitated the selection of these resistant mutants. Thus, as a result, subsequent food preservation treatments of these bacterial cultures might be less effective than expected for WT cultures. In conclusion, this study recommends that treatment with ICs at sub-inhibitory concentrations should be generally avoided, since it could favor the emergence of hyper-resistant strains. To ascertain the true value of EOs and their ICs in the field of food preservation, further research thus needs to be conducted on the induction of increased transient and stable bacterial resistance via such antimicrobial compounds, as revealed in this study.